Opportunities for innovation and intervention in Uganda’s dairy value chain: A scoping report - Ariong, Richard M.; Van Campenhout, Bjorn (International Food Policy Research Institute, 2024)
This report is generated as part of a scoping study to identify possible areas that should be prioritized for intervention to improve performance and sustainability of the dairy industry in Uganda. The evaluation relies on primary and secondary data collected by IFPRI and DDA in 2021. Ten primary datasets are used for the results informing the several interventions and secondary data relies on literature review and Uganda Revenue Authority (URA) dataset. The results underline five issues namely low productivity, low milk quality, and constrained markets. Low productivity is associated with production systems that undermine pasture improvement, disease control and animal health, yet these are primary drivers of milk output notwithstanding breed and effects of climate shocks. Secondly, milk production practices are directly linked to milk quality and low milk quality has negative chain effect on productivity/performance of all actors in the dairy value chain with consequence of low competitiveness of Uganda’s dairy products. The evidence suggests that there is need to explore new approaches to improve productivity and innovations in design of interventions in a holistic value chain approach to improve market performance. To improve production, innovations in livestock management and animal health coupled with milk volume (MV) based rewards are proposed. To improve milk quality, the establishment of qualitybased incentives are proposed.